Small Intestinal Digestive Functions and Feed Efficiency Differ in Different Pig Breeds - Yating Cheng; Sujuan Ding; Md. Abul Kalam Azad; Bo Song; Xiangfeng Kong (Animals, 2023)
Small intestinal growth and health affect its digestion and absorption ability, while little information exists about the small intestinal morphology and function differences among the different pig breeds. Therefore, 90 healthy 35 days of age Taoyuan black (TB), Xiangcun black (XB), and Duroc (DR) pigs (30 pigs per breed) with similar body weight (BW) of the same breed were reared to 185 days of age to evaluate the potential relationship between feed efficiency and small intestinal morphology and function at 80, 125, and 185 days of age. The results show that the TB and XB pigs had lower initial and final BW, ADG, and ADFI and plasma CHO and LDL-C levels, whereas they had higher plasma LIP levels and jejunal trypsin, invertase, lactase, and maltase activities and higher DM, ADF, Tyr, Arg, and His digestibility at 80 days of age compared with the DR pigs. At 125 days of age, TB and XB pigs had lower apparent total tract digestibility and plasma CHO, HDL-C, LDL-C, and NH3 levels; XB pigs had lower DM and NDF digestibility, and TB pigs had higher jejunal lactase and maltase activities. At 185 days of age, TB and XB pigs had lower DM, EE, ADF, and GE digestibility, while having higher plasma ALT and UN levels; TB pigs had higher plasma AST level and jejunal chymase activity. Furthermore, the plasma free amino acid contents, small intestinal VH, and nutrient transporter expression levels differed at different ages. Therefore, the different pig breeds exhibited significantly different growth performance and small intestinal growth, mainly resulting from the differences in digestive enzymes and nutrient transporters in the small intestine.